Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Flexural performance of CFRP grid-reinforced ultra-high performance concrete (UHPC) plates under cyclic incremental loading - JinJing Liao; Haotian Li; Yu Zheng; Linna Geng; Yan Zhuge; Jun-Jie Zeng (Engineering Structures, 2026)

Quasi-pure-phase 2D perovskites for high-efficiency and stable 2D/3D perovskite heterojunction solar cells - Fei Wu; Yuping Gao; Ye Zeng; Junhong Tan; Cheng Zhong; Xing Gao; Yingguo Yang; Yongsheng Liu; Linna Zhu (Chemical Engineering Journal, 2025)

Microbial phosphorus demand affects carbon-degrading potential under long-term nitrogen addition in a subtropical forest - Linna Chen; Quanxin Zeng; Qiufang Zhang; Biao Zhu; Yuexin Fan; Xiaochun Yuan; Yuehmin Chen (Applied Soil Ecology, 2025)

Dynamic simulation of core power control for SPWR based on dynamic model bank - Zheng Li; Xiaoyu Li; Linna Wang; Wenjie Zeng (Annals of Nuclear Energy, 2025)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.

Copper/gold-modified porphyrinic metal–organic frameworks nanoprobes for enhanced photodynamic/chemodynamic therapy - Jiahe Zhang; Linna Chang; Ran Hao; Gangwan Zhang; Tao Liu; Zekai Li; Tianyou Wang; Leyong Zeng (Chemical Engineering Journal, 2023)

Mixed-linker MOFs-derived cross-linked copolymer electrolyte enables high lithium mobility for dendrite-free all-solid-state batteries - Jia Zhou; Xingfa Zeng; Linna Dong; Liya Chen; Xiangrong Wei; Yang liu; Liyi Shi; Le Yu; Jifang Fu (Chemical Engineering Journal, 2023)

Sensitivity analysis of heat transfer coefficient in primary system for LMSR core power control system based on Sobol’s method - Lehua Liang; Chuhao Li; Linna Wang; Xuejian Wang; Wenjie Zeng; Run Luo (Annals of Nuclear Energy, 2023)